2017
DOI: 10.1177/1558944717701241
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence Regarding Routine Antibiotic Prophylaxis in Hand Surgery

Abstract: Based on the current literature, the authors recommend the following patient characteristics not receive antibiotics: clean hygienic patients, without autoimmune disease, and those not taking steroid medication. Surgical characteristics that would render prophylaxis unnecessary include those without hardware, those without reasonable risk of hematoma formation, or those performed at an ambulatory surgery center as opposed to a large hospital. However, the decision should be made on a case-by-case basis weighin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 54 publications
0
30
0
3
Order By: Relevance
“…There is limited and conflicting evidence to support SAP for diagnostic and therapeutic shoulder and knee arthroscopy [23][24][25] and hand surgery. 26 National and international guidelines do not recommend the use of SAP in routine arthroscopic procedures unless the procedure involves insertion of prosthetic material or avascular tissue. 12,13,27 Our study identified that these procedures had the highest rates of procedural inappropriateness due to administration when not required: shoulder (45.4%), knee (72.6%), and hand surgery 65.4% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited and conflicting evidence to support SAP for diagnostic and therapeutic shoulder and knee arthroscopy [23][24][25] and hand surgery. 26 National and international guidelines do not recommend the use of SAP in routine arthroscopic procedures unless the procedure involves insertion of prosthetic material or avascular tissue. 12,13,27 Our study identified that these procedures had the highest rates of procedural inappropriateness due to administration when not required: shoulder (45.4%), knee (72.6%), and hand surgery 65.4% (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…While routine use of antibiotics is not necessary in hand surgery, there are some procedures that do require prophylaxis, such as those that involve the application of metal implants. 6,10,15,19,21 At present, high-level evidence remains absent in the existing literature regarding the administration of prophylactic antibiotics for a clean, elective, nonarthroplasty surgery and its impact on reducing postoperative surgical site infections. The development of antibiotic resistance, adverse reactions to the antibiotics, and cost are often cited as factors in deciding against the routine use of antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dunn et al, in a review of current evidence of prophylaxis, cite multiple studies describing rates of up to 26% of adverse reactions to antibiotic administration. 10 A careful review of these references reveal that most of the antibiotics used in these studies are not typically used for prophylaxis during outpatient surgery, including amoxicillin/clavulanate and ciprofloxacin. Moreover, the setting for these studies was generally in inpatient burn units, where patients with other, significant comorbidities may be more likely to result in adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are selective [5] and even systematic [1] reviews on antibiotic use before clean surgery, but they are based on surprisingly sparse evidence. For that reason, we are excited to publish this month's spotlight article, "Effectiveness of Preoperative Antibiotics in Preventing Surgical Site Infection After Common Soft Tissue Procedures of the Hand," by Dr. Robin Kamal's group at Stanford University [9].…”
mentioning
confidence: 99%